Investment opportunity set and dividend policy in Malaysia : some evidence on the role of government ownership, family ownership, board size and board composition / Ravichandran K. Subramaniam. - Subramaniam, Ravichandran K. (2011)
Prior studies show that there is a negative association between IOS (Investment opportunity set) or growth opportunities and dividend payout. While there are several theories such as the signalling hypothesis, the tax hypothesis, free cash flow (FCF) hypothesis and the contracting hypothesis that maybe used to explain this relationship, the main theory suggested in the extant literature was Free Cash Flow Theory (FCF) by Smith and Watts (1992). According to the free cash flow theory, managers of firms with more growth opportunities or higher IOS (prospective investment opportunities and associated payoff distributions) are more likely to pay lesser dividends since these firms need the cash for growth opportunities. However, firms with low growth opportunities pay out more dividends since these firms have few opportunities to invest in positive net present value projects. In this study I re-examine whether this negative relationship exists in the Malaysian corporate sector. I examine Malaysian firms because it is a developing country and also because of the existence of a global decline in the propensity to pay dividends especially among firms incorporated in common law jurisdictions. Further I investigate whether corporate governance variables such as (1) government ownership (2) boardsize, (3) board composition and (4) family ownership affects the association between growth opportunities and dividend policies. I examine government ownership because there seemed to be a high concentration of government link companies among public listed companies. Board-size and board composition is examined to evaluate to what extent those corporate governance monitoring have an impact on dividend payouts. No known prior study has investigated whether these variables moderate the relationship between growth opportunities and dividend payout. Several hypotheses are developed to test these relationships. Using data from annual reports of Malaysian companies I expect to find that there is a negative association between growth opportunities and dividend payout in Malaysian firms thus confirming prior findings and FCF theory. Further I expect that the relationship should be weaker for government owned as there is some anecdotal evidence suggesting a positive association between ownership and dividends since firms with government ownership have relatively less difficulty raising funds to finance investments and can therefore afford to pay dividends. As for family owned businesses, the relationship would be weaker because of the high concentration of family ownership as family members are concerned about wealth transfer. The relationship for board-size and board composition is envisaged to be negatively related to growth opportunities.